A report of two infant cases operated for jejunal duplication cyst associated with malrotation and volvulus. (2020) - Azzam, Ahmed; Abdulkarim, Ali N.; Shehata, Ahmed E.M.; Mahran, Ibrahim; Arafa, Ahmed; Arafat, Ahmed; Tawfik, Sherifa; Shaban, Muayad; Anache, Aliyu; Kaddah, Sherif; Taher, Heba
Highlights: THE COMBINATION OF Enteric duplication and intestinal malrotation IS rare but can coexist. Malrotation MUST BE kept in mind in patients with preoperatively diagnosed duplication cyst. Surgical correction in form of A LADD's procedure and resection of THE duplication WITH anastomosis IS CURATIVE. Ultrasound seems TO BE a good diagnostic tool for THE PREOPERATIVE diagnosis of both conditions. Abstract: Introduction: Both Enteric duplication and intestinal malrotation are concerning causes for intestinal obstruction in the pediatric age group and they very rarely coexist in the same patient. Presentation of cases: We present 2 cases of previously healthy children, the first is a 4-month-old infant and the second is a 1.5-year-old boy, both presented with recurrent attacks of bilious vomiting that proved to be due to acute midgut volvulus caused by an enteric duplication cyst associated with intestinal malrotation. Discussion: Enteric duplication and intestinal malrotation are two of the concerning causes of billious vomiting in the pediatric age group. They could be encountered at any level of the alimentary tract from the tongue to the anus. The term malrotation refers to all abnormalities of intestinal position. The coincidence of intestinal malrotation and an enteric duplication cyst (EDC) is very rare and has been described only in a few case reports. Conclusion: The concomitance of EDC and intestinal malrotation is extremely rare and should be kept in mind in a child presenting with bilious vomiting especially in a child preoperatively diagnosed with a duplication cyst.